“Pitch Lake”. Trinidad. B.W.I. - (:unkn) unknown (My University, 2010)
The Pitch Lake, La Brea, south west Trinidad. Numerous trees are spread across the horizon. The Pitch Lake is the largest natural deposit of asphalt in the world. It was discovery by Sir Walter Raleigh in 1595. It is mined for asphalt and is a fascinating tourist attraction.
Colour: Sepia; Style: Landscape; Other: Bordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Cities and towns--Trinidad and Tobago--Brighton; Cities and towns--Trinidad and Tobago--La Brea; Asphalt industry--Trinidad and Tobago; Pitch; Buildings--Trinidad and Tobago; [1930]; Pitch Lake, The (La Brea)